Factors Related to Infection in Systemic Lupus Erythematosus PatientsAdmitted to the Hospital - Laniyati Hamijoyo (Indonesian Rheumatology Associantion, 2022)
Background: One of the causes of the increase in hospitalized SLE patientsis infection, and it is an important factor in morbidity and mortality, so it isnecessary to conduct a research to identify factors related to infection andthe type of infection caused in hospitalized SLE patients. Methods: Thisstudy is a retrospective, categorical descriptive study utilizing medicalrecords of SLE patients diagnosed with and treated for infection both onadmission and during their stay in Hasan Sadikin General Hospital betweenJanuary 2016 to June 2018. Results: Seventy- four patients were involvedinto this study. Female were 70 (94.6%), aged <40 years were 69 (93.2%)patients, and all 74 (100%) were entirely in an active disease condition witha mean Mexican systemic lupus erythematosus disease activity (MexSLEDAI) score of 9 ± 5.2. Fifty-three (71.6%) subjects experienced majorinfections. Mucocutaneous and kidney were the most organs involvementfound in SLE patients during infection, 63 (85.1%) and 57 (77.0%)respectively. Sixty-two (83.7%) subjects had received corticosteroids beforethe onset of infection, while pneumonia was the most common infectionfound in 33 patients (44.6%). This study also noted 12 (16.2%) patientsdeceased related to infection with most causes were respiratory failure(66.7%). Conclusion: Age less than 40-year-old, mucocutaneous and kidneyinvolvement and previously on corticosteroids were found higher among inhospitalized SLE patients. Most experienced major infections andpneumonia is the most common type of infection.